PENANGANAN COVID-19 DI PONDOK PESANTREN TANBIHUL GHOFILIN BANJARNEGARA DENGAN PARADIGMA MIT AMIN ABDULLAH - Abas Zahrotin (Aplikasia)
One of the steps to deal with Covid-19 in Indonesia is hampered by public disorder in carrying out health protocols. The disorder starts from not believing in the existence of Covid-19 and or using a single religious reasoning in reading the Covid-19 pandemic. At the Tanbihul Ghofilin Islamic Boarding School Banjarnegara, the handling of Covid-19 has been quite good and has received an award from the Governor of Central Java as the second best Islamic boarding school in Central Java in handling Covid-19. Prof. Dr. Amin Abudullah, MA, namely multidisciplinary, interdisciplinary, and transdisciplinary (MIT), is applied as a paradigm that develops success in handling Covid-19. Handling Covid-19 itself is not only prevention, but also handling if students are exposed to Covid-19.